Clickbait dalam Pemberitaan Penyusunan Kabinet Prabowo-Gibran pada Media Siber Tribunnews - Ummu Nabiela Qurrota Aini; Sri Mustika; Andys Tiara (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
This study evaluates the use of clickbait in the reporting of the Prabowo-Gibran cabinet formation by the online media outlet Tribunnews. Utilizing a qualitative content analysis approach, the research examines 18 news articles published between September 23 and October 20, 2024. The study finds that focusing on popular topics or figures and the use of sensational language are frequently employed to attract readers, even though the content does not always meet the expectations set by the headlines. The study applies Harold Lasswell's communication model to analyze how clickbait usage influences public perception. It concludes that while clickbait increases revenue through higher traffic, excessive use can undermine trust in the media. Future research is recommended to explore the long-term impact of clickbait on media credibility and to conduct comparative studies across various online media platforms to provide a broader perspective on this phenomenon in Indonesia's digital media landscape.